The Influence of Reward on Turnover Intention with the Organizational Commitment as an Intervening Variable (A Study on Group I and II Employee at Djatiroto Sugar Factory) - Arianto, A; ., Syihabudhin (KnE Social Sciences, 2018)
Turnover Intention is an early signal of potential employee turnover within the company. Attempts to detect a turnover intention is important to do because qualified human resources need to be maintained for the sake of the company’s progress. This study aims to determine the condition of reward variables, organizational commitment, and Turnover Intention, as well as the influence of reward variables and commitment to Turnover Intention on the employees of Djatioroto Sugar Factory in Lumajang. By using proportional random sampling method, respondents in this study were 217 people from 472 employees of Group I and II Djatioroto Sugar Factory, Lumajang. Using path analysis, the results showed that there was a significant direct effect of rewards on turnover intention, rewards to organizational commitment, and organizational commitment to turnover intention. In addition, there is an indirect influence of rewards on turnover intention, with organizational commitment as an intervening variable. Keywords: Reward, Organizational Commitment, Turnover Intention.